Picuris Indians open abandoned pueblo (Taos, NM Taos News, 1972)
Talking about the reconstruction and excavation of the Picuris Pueblo, also known as San Lorenzo Pueblo, and about what they plan to do afterwards.
Front side of Newspaper article
Master list item #: 98
File location is in the New Mexico file Cabinet
Keywords: Picuris Indians; Indian Restoration; Indian Excavation; Indian History; Indian Life and Customs; San Lorenzo Pueblo; Picuris Pueblo